A Monolithic CMOS-MEMS Reconfigurable/Tunable Capacitive Accelerometer with Integrated Sensing Circuits - Chiu, Yi; Lin, Cheng-Yen; Hong, Hao-Chiao (Frontiers in Mechanical Engineering, 2022)
MEMS accelerometers have been widely used in various applications with a wide range of signal levels and bandwidth. Therefore it is desired to have a sensor whose characteristics such as sensitivity and bandwidth can be reconfigured/tuned depending on specific applications. This paper presents a reconfigurable/tunable z-axis accelerometer whose mechanical resonant frequency, sensitivity and sensing bandwidth can be tuned by the electrostatic spring softening effect. The proposed accelerometer was designed using a commercial 0.35 um CMOS foundry service. The tuning electrodes were implemented in the metal and polysilicon layers in the standard CMOS process. An on-chip chopper stabilized readout circuit was designed to convert the capacitance signal to a voltage readout. The sensing structure was released by post-CMOS wet metal etching. Measurement results showed the proposed accelerometer had a sensitivity of 12 mV/g in the range of 0 to 5 g. The sensitivity and bandwidth tuning ranges are 50% and 18%, respectively, for an applied tuning voltage of 25 V. The demonstrated device is the first reconfigurable/tunable CMOS-MEMS accelerometer in the literature to our best knowledge.